Study of population dynamics of Clavibacter michiganensis subsp. michiganensis in exposed and buried crop debris - Ayesha Bibi; Muhammad Junaid; Musharaf Ahmad; Syed Fayaz Ali Shah; Iftikhar Hussain Khalil (Novel Research in Microbiology Journal)
The aims of the current work were to determine the effect of burial depth (0, 6, 12 and 18 cm) on the degradation of diseased crop debris, and survival of the debris-borne bacterial inoculum. This study was carried out in two-locations namely; the Agricultural Research Institute, Tarnab, Peshawar, and the Haripur University, Haripur campus, Pakistan. Results revealed that the debris degraded at faster rate and the number of bacteria per gram of tissue declined more in buried samples than in exposed samples. Moreover, the decline in number of bacteria was more at greater depths than at shallow ones; suggesting that the use of turn-over ploughs after harvest would be helpful in reducing the crop debris-borne primary inoculum, and hence reducing the disease incidence. During a period of 270 days, the mean number of cells of Clavibacter michiganensis subsp. michiganensis (Cmm)\ gram of exposed stem tissue was reduced from 8.9×109 to 6.0×105 at ARI, Tarnab, and from 7.93×109 to 5.26×105 at Haripur. On the other hand, the mean number of cells\ gram of tissue at ARI, Tarnab buried at different soil depths of 6, 12, and 18 cm, decreased from 9.05×109 to 3.2×103 , 8.55×109 to 2.9×103 , and 5.8×109 to non-detectable; respectively, after 270 days of burial. Whereas at Haripur; the mean number of cells\ gram of tissue buried at the same depths decreased from 4.28×109 to 1.81×104 , 4.46×109 to 2.31×103 , and 3.82×109 to non-detectable, respectively, after the same period.